Selecting A Cyclic Redundancy Check (CRC) Generator Polynomial for CEH (CRC Extension Header). - Supriyanto, Supriyanto; M. Taib, Abidah; Budiarto, Rahmat (2009)

(untitled)
Computation and regeneration of CRC code in each router may cause slower IPv6 packet transmission.